PEMBELAJARAN KIMIA BERBASIS PROBLEM SOLVING MENGGUNAKAN LABORATORIUM RIIL DAN VIRTUAL DITINJAU DARI GAYA BELAJAR DAN HASIL BELAJAR PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Rizki Aryanti; Muhammad Kusasi (Universitas Lambung Mangkurat, 2016)
Abstract.: A research on the chemical-based learning problem solving using real and virtual laboratory in terms of learning styles and learning outcomes in the electrolyte solution and Non-electrolytes material class X. This study aims to (1) determine differences in learning outcomes, (2) a description of evidence tendency learning styles, and (3) the response of students between classes with chemical-based learning problem solving using real lab and classes using virtual labs. Methods The study was a quasi-experimental design with nonequivalent control group design. Samples were class X-7 as a learning experiment with using a virtual lab and X-4 as a control by learning using real lab. Collecting data using the testing techniques, observation and questionnaires. Data were analyzed using t-test, correlation and descriptive analysis. T-test was used to analyze differences in cognitive achievement grade students experiment with the control class. Correlation test was used to analyze the relationship between learning outcomes with students' learning styles. The results showed that (1) there are differences in cognitive learning outcomes significantly between grade students experiment with the control class, (2) kinesthetic tend to laboratory real while the visual and auditory tend to virtual labs, and (3) learning based chemistry problem solving using a laboratory the real and virtual received a positive response from the students on the material electrolyte solution and Non-electrolytes.Keywords: problem solving, real and virtual labs, learning outcomes, learning style.